2005
DOI: 10.1086/497357
|View full text |Cite
|
Sign up to set email alerts
|

Deep Near‐Infrared Imaging and Photometry of the Antennae Galaxies with WIRC

Abstract: We present deep near-infrared images of the Antennae galaxies, taken with the Palomar Wide-Field Infrared Camera (WIRC). The images cover a 4A33 ; 4A33 (24:7 ; 24:7 kpc) area around the galaxy interaction zone. We derive J-and K s -band photometric fluxes for 172 infrared star clusters and discuss details of the two galactic nuclei and the overlap region. We also discuss the properties of a subset of 27 sources that have been detected with WIRC, HST, and the VLA. The sources in common are young clusters of les… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 19 publications
8
28
0
Order By: Relevance
“…This basically agrees with star cluster age distributions given by Kassin et al (2003), Brandl et al (2005), and Mengel et al (2005). The locations of these sites of star formation all do not coincide with the CO clouds.…”
Section: Near-infraredsupporting
confidence: 85%
“…This basically agrees with star cluster age distributions given by Kassin et al (2003), Brandl et al (2005), and Mengel et al (2005). The locations of these sites of star formation all do not coincide with the CO clouds.…”
Section: Near-infraredsupporting
confidence: 85%
“…We found that this knot has infrared colors even warmer than that of the YSCC in ARP 24, based on archival Spitzer data (PI: G. Fazio; see also Wang et al 2004). Its very red near-infrared color (J − Ks = 1.86) indicates that it suffers from heavy dust extinction (Brandl et al 2005). Thus, we speculate that some star clusters in galaxies which are very young and optically faint caused by heavy dust extinctions may also have warm infrared colors like the YSCC we found in ARP 24.…”
Section: Pah and Warm Dust Emissionmentioning
confidence: 49%
“…This system is one of the most spectacular examples of gas-rich major mergers as well as being the closest (distance=22±3 Mpc, Schweizer et al 2008). The system has a total infrared luminosity of log(L ir /L ) = 10.86 (Sanders et al 2003) approaching that of a luminous infrared galaxy, and is subject of heavy and variable attenuation (Brandl et al 2005). It therefore presents a good target for the search of extragalactic DIBs.…”
Section: Introductionmentioning
confidence: 99%